Monitoring and dietary exposure assessment of chloropropanol esters and glycidyl esters in infant formula sold in Shanghai City - YU Shenghao; LI Yiqi; ZHANG Lujing; PENG Shaojie (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveWe aimed to evaluate the dietary exposure risk to infants by investigating the chloropropanol ester （MCPDE） and glycidyl ester （GE） contamination levels in infant formula sold in Shanghai City.MethodsThe dietary exposure of 3-MCPDE， 2-MCPDE， and GE for infants through infant formula was assessed by the point assessment method according to the risk monitoring data of MCPDE and GE in 90 infant formula sold in Shanghai City in 2020 and the dietary consumption data of infants.ResultsThe detection rates of 3-MCPDE， 2-MCPDE， and GE in infant formula sold in Shanghai City were 100%， 100%， and 12.2%， respectively. The mean contents were 0.084， 0.021， and 0.005 mg/kg， and the maximum values were 0.231， 0.034， and 0.031 mg/kg， respectively. The mean and 95 percentile values of daily 3-MCPDE intake of infants aged 0-6 months in Shanghai City through infant formula were 1.262 and 2.166 μg/kg·BW， accounting for 63.1% and 108.3% of the tolerable daily intake （TDI） of 3-MCPDE （2 μg/kg·BW）， respectively. The mean and 95 percentile value of daily 3-MCPDE exposure of infants aged 6-12 and 12-36 months through infant formula were lower than the TDI value. The mean value of daily 2-MCPDE exposure of infants in different month-age groups through infant formula were 0.118-0.319 μg/kg·BW. The margin of exposure values of mean and 95 percentile of daily GE exposure of infants in different month-age groups through infant formula were greater than 10 000.ConclusionFor infants and young children aged 0-36 months in Shanghai City， the health risks of daily intake of 3-MCPDE and GE through infant formula were generally at an acceptable level. However， for infants aged 0-6 months with high food consumption， the health risk of exposure to 3-MCPDE through infant formula merits further evaluation.